2021
DOI: 10.3389/fpls.2021.614926
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Shoot Architecture Traits in Edamame Reveals Potential Strategies to Improve Harvest Efficiency

Abstract: Edamame is a type of green, vegetable soybean and improving shoot architecture traits for edamame is important for breeding of high-yield varieties by decreasing potential loss due to harvesting. In this study, we use digital imaging technology and computer vision algorithms to characterize major traits of shoot architecture for edamame. Using a population of edamame PIs, we seek to identify underlying genetic control of different shoot architecture traits. We found significant variations in the shoot architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Lara (2016) identified SNPs associated with SW, sucrose content, and protein content; Zhao et al (2019) reported SNPs associated to soybean seed shape; and Dhakal et al. (2021) identified SNPs associated with shoot architecture traits which can improve edamame harvestability. According to Grant et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lara (2016) identified SNPs associated with SW, sucrose content, and protein content; Zhao et al (2019) reported SNPs associated to soybean seed shape; and Dhakal et al. (2021) identified SNPs associated with shoot architecture traits which can improve edamame harvestability. According to Grant et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of skeletonisation as part of a morphological analysis pipeline using RGB images or images derived from visible-spectrum imagery is less common. Examples where this has been used include the phenotyping of roots [ 34 ], mapping of branching in edamame [ 35 ], the identification of legumes based on leaf venation [ 30 ], identification of the structure of maize tassels [ 36 ] and branches in roses for the purposes of training a robot to undertake pruning [ 37 ]. Our work is the first example of using skeletonisation from RGB images to map branching in dicotyledonous species.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetable soybean has been extensively used for more than 2000 years in East Asian countries [ 3 ]. In recent years, acceptance of vegetable soybean-based food products has been reported in North and South America, Europe, and Africa [ 4 ]. Vegetable soybean has become a popular food all over the world because of their taste and nutritional value.…”
Section: Introductionmentioning
confidence: 99%